METHODS OF TEACHING ENGLISH AND EASY WAYS TO LEARN ENGLISH - Ramazonov , Shohruh Nusratillo o‘g‘li (Educational Research in Universal Sciences, 2023)
A language teaching method is a single set of procedures which teachers are to follow in the classroom. Methods are usually based on a set of beliefs about the nature of language and learning.’ (Noonan, 2003, p. 5). Ask teachers what method they subscribe to, and most will answer either that they don’t follow a method at all, or that they are ‘eclectic’, and pick and choose from techniques and procedures associated with a variety of different methods. Some might add that, essentially, their teaching follows the principles laid down by the communicative approach, itself a mixed bag, embracing anything from drills to communicative tasks, and everything in between. But the concept of a single, prescriptive ‘method’ - as in the Direct Method, or the Oral Method - seems now to be dead and buried.